Uncovering a novel biosynthetic gene cluster for sordarin through genome mining in the fungus Talaromyces adpressus - Qianqian Xu; Xiaomeng Ren; Linzhen Hu; Qiaoxin Xu; Xiaodong Zhang; Mengyi Deng; Ying Ye; Yonghui Zhang; Yuanyuan Lu; Yuben Qiao (Bioresources and Bioprocessing)
Abstract To explore the chemical and biological diversities of diterpenoids from the fungus Talaromyces adpressus, a previously unknown biosynthetic gene cluster (BGC, tdn) for sordarin (a well-known fungal antibiotics) was discovered by leveraging the genome mining method. Heterologous expressions of key genes of tdn in Aspergillus oryzae, led to the determination of one new diterpenoid, cycloaraneosene-9-ol-8-one (4), and three known diterpenoids, cycloaraneosene (1), cycloaraneosene-9-ol (2), cycloaraneosene-8,9-diol (3). The structures of 1–4 was elucidated well via detailed analysis of 1D and 2D NMR, GCMS, HRESIMS, IR data, and comparison with reported data. Structurally, compounds 1–4 were belonging to fusicoccane diterpenoids with a classical tricyclic 5/8/5 ring system, which are participated in the biosynthesis of sordarin. Compound 4 maybe a key precursor for a Baeyer–Villiger like reaction with C8–C9 bond cleavage in the biosynthetic pathway of sordarin. Moreover, all isolates were evaluated for their bioactivities, compounds 3, and 4 exhibited inhibitory activities against the human cancer cell lines with IC50 values ranging from 7.8 to 32.4 µM. 3 and 4 promote cell apoptosis of HCT-116 and HepG2 cells, and suppress cell migration of HepG2 cells. As well, 3 and 4 also decrease gene expression of cell proliferation related molecules BCL-2 and cyclin D1, while increase expression of cell apoptosis related gene BAX. Targets predication and molecular docking indicate that compound 4 exhibits stronger affinity for DBL, suggesting its excellent binding potential. This finding will be enriched the structures and bioactivities of diterpenoids with a tricyclic 5/8/5 ring system, most importantly, will provide new strategies for the synthetic biological research of sordarins. Graphical Abstract